Hepatic thyroid signaling of heat-stressed late pregnant and early lactating cows. Issue 2 (August 2017) - Weitzel, Joachim M; Viergutz, Torsten; Albrecht, Dirk; Bruckmaier, Rupert; Schmicke, Marion; Tuchscherer, Armin; Koch, Franziska; Kuhla, Björn
Abstract : During the transition between late gestation and early lactation, dairy cows experience severe metabolic stress due to the high energy and nutrient requirements of the fetus and the mammary gland. Additional thermal stress that occurs with rising temperatures during the ongoing climate change has further adverse implications on energy intake, metabolism and welfare. The thyroid hormone (TH)-mediated cellular signaling has a pivotal role in regulation of body temperature, energy intake and metabolic adaptation to heat. To distinguish between energy intake and heat stress-related effects, Holstein cows were first kept at thermoneutrality at 15°C followed by exposure to heat stress (HS) at 28°C or pair-feeding (PF) at 15°C for 6 days, in late pregnancy and again in early lactation. Herein, we focused on hepatic metabolic changes associated with alterations in the hypothalamic–pituitary–thyroid axis in HS and PF animals. T3 and T4 levels dropped with HS or PF; however, in HS animals, this decline was more pronounced. Thyroid-stimulating hormone (TSH) levels remain unaffected, while plasma cholesterol concentrations were lower in HS than PF animals. Hepatic marker genes for TH action ( THRA, DIO1 and PPARGC1 ) decreased after HS and were lower compared to PF cows but only post-partum. Proteomics data revealed reduced hepatic amino acid catabolism ante-partum and a shift toward activated beta-oxidation and gluconeogenesis but declined oxidative stress defense post-partum. Thus, liver metabolism of HS and PF cows adapts differently to diminished energy intake both ante-partum and post-partum, and a different TH sensitivity is involved in the regulation of catabolic processes.